Demanding Justice in The Global South
XV, 210 p. 1 illus.
Keywords: The politics of claiming rights and strategies of mobilisation exhibited by marginalised social groups lie at the heart of this volume. Theoretically, the authors aims to foster a holistic and multi-faceted understanding of how social and economic justice is claimed, either through formal, corporatist or organised mechanisms, or through ad hoc, informal, or individualised practices, as well as the implications of these distinctive activist strategies. The collection emphasises both the difficulties of political mobilisation and the distinctive methods employed by various social groups across a variety of contexts to respond and overcome these challenges. Crucially, the authors’ approach involves a conceptualisation of social movements and local mobilisation in terms of the language of rights and justice claims-making through more organised as well as everyday political practices. In so doing, the book bridges the literature on contentious politics, the politics of claiming social justice, and everyday politics of resistance.